A ratiometric fluorescent biosensor for the sensitive determination of α-glucosidase activity and acarbose based on N-doped carbon dots. Issue 17 (16th July 2020) - Wang, Mengjun; Wang, Mengke; Zhang, Feng; Su, Xingguang
Abstract : A ratiometric fluorescent biosensor for the determination of α-glucosidase and acarbose was constructed based on the N-CDs/PHQ-PEI system. Abstract : In this work, a novel ratiometric fluorescent platform for α-glucosidase (α-glu) and its inhibitor was constructed based on N-doped carbon dots (N-CDs). The α-glucosidase present can catalyze the release of hydroquinone (HQ) from α-arbutin. Then, the generated HQ can be oxidized and copolymerized with polyethyleneimine (PEI) to form a yellowish green fluorescence copolymer (PHQ-PEI ) with intense fluorescence emission at 510 nm. When the PHQ-PEI was formed, blue fluorescence of N-CDs at 425 nm was decreased, whereas the fluorescence of PHQ-PEI at 510 nm increased sharply as a result of the fluorescence resonance energy transfer (FRET) effect between N-CDs and PHQ-PEI . However, in the presence of acarbose, the activity of α-glucosidase is inhibited, and α-arbutin cannot be hydrolyzed to hydroquinone, leading to the fluorescence recovery of N-CDs at 425 nm and the fluorescence decrease of PHQ-PEI at 510 nm. The linear range from 0.2 to 1.6 mU mL −1 and 25–150 μmol L −1 was obtained for α-glucosidase and acarbose detection, respectively, and the detection limit (LOD) for α-glucosidase and acarbose was as low as 0.082 mU mL −1 and 14.5 μmol L −1 . Thus, a ratiometric fluorescent sensor with good sensitivity and high specificity was established for α-glucosidase assay and satisfactory results were acquired in real sample determination.